Interaction of Bordetella adenylate cyclase toxin with complement receptor 3 involves multivalent glycan binding. Issue 3 (29th December 2014) - Hasan, Shakir; Osickova, Adriana; Bumba, Ladislav; Novák, Petr; Sebo, Peter; Osicka, Radim
Abstract : The interaction of Bordetella pertussis adenylate cyclase toxin (CyaA) with complement receptor 3 (CR3, CD11b/CD18) involves N‐linked oligosaccharide chains. To investigate the relative importance of the individual N‐glycans of CR3 for toxin activity, the asparagine residues of the consensus N‐glycosylation sites of CR3 were substituted with glutamine residues that cannot be glycosylated. Examination of CR3 mutant variants and mass spectrometry analysis of the N‐glycosylation pattern of CR3 revealed that N‐glycans located in the C‐terminal part of the CD11b subunit are involved in binding and cytotoxic activity of CyaA. We suggest that these N‐glycans form a defined clustered saccharide patch that enables multivalent contact of CR3 with CyaA, enhancing both affinity and specificity of the integrin–toxin interaction. Abstract : CR3 (CD11b/CD18) is glycosylated at the majority of predicted N‐glycosylation sites. A set of 25 CR3 mutant variants lacking individual N‐glycans was generated. The importance of individual N‐glycans in interaction of CR3 with CyaA was explored. N‐glycans at the C‐terminus of CD11b were involved in binding and cytotoxic activity of CyaA.